UNVEILING THE RHETORIC: ANALYZING ILLOCUTIONARY ACTS IN ANIES BASWEDAN’S 2024 PRESIDENTIAL CAMPAIGN “DESAK ANIES” PROGRAM - Edel, Eky Erlanda; Dian Dia-an Muniroh, R; Sasnitya, Raden (Jurnal Kata, 2025)
The research objectives are to describe the types of illocutionary acts in Anies Baswedan’s utterances in the political context as a pragmatic analysis. This descriptive qualitative research collected and analyzed the data using Searle’s theory of Illocutionary Acts (2005) and Levinson’s theory of the context (1983) using 30 utterances from the “Desak Anies” program conducted in Semarang and uploaded by Metro TV to its official YouTube channel a week before election day. The research findings revealed that the most used illocutionary acts by Baswedan in the “Desak Anies” program were assertives, for 45%, used to describe the world or convey information that the speaker believes to be true. Assertive utterances aim to inform, describe, or explain and are evaluated based on truthfulness or accuracy. Assertive utterances are key communication components that help share knowledge and convey facts. Baswedan is known for his rhetorical speech and his skills in speaking to persuade or convince audiences. Baswedan uses examples, facts, and logical explanations to support his ideas/ opinions in that part.